2015
DOI: 10.1002/jmv.24256
|View full text |Cite
|
Sign up to set email alerts
|

Sites of disruption within E1 and E2 genes of HPV16 and association with cervical dysplasia

Abstract: Integration of HPV16 DNA into the host chromosome usually disrupts the E1 and/or E2 genes. The present study investigated the disruption of E1, E2 genes in a total of eighty four HPV16-positive precancerous and cervical cancer specimens derived from Greek women (seventeen paraffin-embedded cervical biopsies and sixty seven Thin Prep samples). Complete E2 and E1 genes were amplified using three and nine overlapping primer sets respectively, in order to define the sites of disruption. Extensive mapping analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 47 publications
0
37
0
Order By: Relevance
“…Although HPV16 and 18 are considered to be the most prevalent HPV types contributing to cervical cancers worldwide, HPV18 is not the most common genotype in Asian countries and our previous results suggested that HPV16 and 52, instead of HPV18, are the top two prevalent types in Shanghai women [36]. The viral DNA is usually found to integrate into the host genome with subsequent disruption of one or more viral open reading frames (ORFs) [7]. HPV integration frequently disrupts in the E1 and/or E2 ORFs.…”
Section: Introductionmentioning
confidence: 99%
“…Although HPV16 and 18 are considered to be the most prevalent HPV types contributing to cervical cancers worldwide, HPV18 is not the most common genotype in Asian countries and our previous results suggested that HPV16 and 52, instead of HPV18, are the top two prevalent types in Shanghai women [36]. The viral DNA is usually found to integrate into the host genome with subsequent disruption of one or more viral open reading frames (ORFs) [7]. HPV integration frequently disrupts in the E1 and/or E2 ORFs.…”
Section: Introductionmentioning
confidence: 99%
“…The E6 gene may be present in both episomal and integrated forms, playing a key role in malignant transformation (15), or may remain just as a persistent and harmless DNA fragment after a resolved infection (16,35). Integration usually hits other, less attractive targets at different sites in E1, E2, L1 and L2 regions (10,14,20,21,36) and potentially reduces the sensitivity in HPV detection (37).…”
Section: Discussionmentioning
confidence: 99%
“…The reverse primers were constructed for each fragment in order to get smaller fragments from FFPE tissues (80 bp for E6 and 97 bp for L1). E1 primers were designed inside the coding region, most frequently disrupted during viral integration in the host chromosome (14,32), in order to get a fragment of 168 bp.…”
Section: Hpv Detection By Pcr Ihc and Ishmentioning
confidence: 99%
“…It has been demonstrated clearly that expression E1 and E2 proteins from different HPV genomes can induce replication of the genomic integrated HPV origin [30], and this is a particular danger in the presence of DNA damage [31]. Then, anti-HPV agents unblocking viral DNA synthesis could, in time, benefit cancer development increasing HPV genome integration.…”
Section: Hpv Life Cyclementioning
confidence: 99%